2022
DOI: 10.3390/ma16010389
|View full text |Cite
|
Sign up to set email alerts
|

Production of Activated Biochar Derived from Residual Biomass for Adsorption of Volatile Organic Compounds

Abstract: Volatile organic compounds (VOCs) released in air represent a major potential for environmental pollution. Capture methods based on activated biochar have attracted attention because of their low cost and for the high removal capacity of the material due to its physical and chemical properties. In this paper, activated biochars were developed and their adsorption performance for VOC capture was evaluated. In the first step, biochars derived from rapeseed cake (RSC) and walnut shells (WSC) were obtained through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Toluene has an aromatic ring with a methyl group. It has a strong affinity to oxygen‐containing functional groups, as their presence is predicted in analysis (David, 2022).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Toluene has an aromatic ring with a methyl group. It has a strong affinity to oxygen‐containing functional groups, as their presence is predicted in analysis (David, 2022).…”
Section: Resultsmentioning
confidence: 79%
“…Shagali et al (2021) treated walnut biochars using KOH and observed the functional groups like stretching alkenes and hydroxyl and aldehyde groups. David (2022) treated walnut shell biochar and performed FTIR, showing CO group from esters and ethers. In the present study, FTIR showed adsorption bands in CO in ketones, carboxyl group, and free OH group.…”
Section: Resultsmentioning
confidence: 99%